Mobil és okos - Mátó, Áron (Kultúratudományi Szemle, 2024)
Mobil and Smart - Moral Philosophical Unknows in the (smart)phone use The mobility and intelligence of smartphones make it an ethical actor. The smartphone, as a portable personal computer, provides easy access to the realm of the internet. As a result, the smartphone becomes an unprecedented extension of our mind, a 21st-century umbilical cord. This essay discusses four ethical-philosophical problems that interpret the smartphone and its phenomenon through philosophical systems and paradoxes. The first problem arises in relation to time, where, alongside the internal contradictions of usage, the smartphone can be interpreted as the embodiment of vulgar time in Heidegger's concept of time, and it also transforms our perception of time.